2002
DOI: 10.1097/00005110-200202000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Nursing Practice, Part 2

Abstract: Numerous articles describe barriers to nurses conducting research and achieving evidence-based practice as well as strategies for overcoming barriers. The Research Roundtable format is one such strategy. It is an interactive means for providing novice nurse researchers and nursing students with the skill sets required to drive application of existing evidence to nursing practice and conduct outcome studies to derive new evidence. The authors discuss their Research Roundtable series that addressed a number of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…For this reason, together with the insufficient manpower, high workload and time constraints, Chinese nurses may perceive there to be many inhibitors of research utilization or evidence-based practice, such as ‘the facilities are inadequate for implementation’, ‘the results are not generalizable to our own setting’ and ‘the administration will not allow implementation’, which were rated as three of the top 10 barriers by the nurses in this study. The utmost importance of organizational support for research utilization should be reinforced by establishing innovative strategies and sufficient resources and facilities for research implementation such as setting up centers for research and evidence-based practice, clearly defined guidelines for research implementation and utilization in clinical areas and more opportunities for nursing research training [18,37]. These supportive strategies can in turn nurture research appraisal and a culture for research utilization in different clinical areas [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, together with the insufficient manpower, high workload and time constraints, Chinese nurses may perceive there to be many inhibitors of research utilization or evidence-based practice, such as ‘the facilities are inadequate for implementation’, ‘the results are not generalizable to our own setting’ and ‘the administration will not allow implementation’, which were rated as three of the top 10 barriers by the nurses in this study. The utmost importance of organizational support for research utilization should be reinforced by establishing innovative strategies and sufficient resources and facilities for research implementation such as setting up centers for research and evidence-based practice, clearly defined guidelines for research implementation and utilization in clinical areas and more opportunities for nursing research training [18,37]. These supportive strategies can in turn nurture research appraisal and a culture for research utilization in different clinical areas [10].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this guidelines or policy, adequate organizational support for research appraisal and utilization should be reinforced by establishing innovative strategies and sufficient resources and facilities for research implementation such as setting up centers for research and evidence-based practice and clearly defined guidelines for research implementation and utilization in clinical areas. Research-based practice can also be set as an expectation of ‘usual’ nursing practice, and rewards can be offered to those who have demonstrated successful research implementation and utilization in their practices [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Evridiki Patelarou 1,2 , Konstantinos Vlasiadis 3 , Mariusz Panczyk 1,4 , Jakub Dolezel 1,5 , Darja Jarosova 1,5 , Joanna Gotlib 1,4 , Brigita Skela-Savič 1,6 , Daniela Mecugni 1,7 , Stefano Finotto 1,7 , Maria Ruzafa-Martinez 1,8 , Antonio Jesús Ramos-Morcillo 1,2 , Athina Patelarou 1,2 nursing has been slow and remains a challenge to the profession. Across different countries, research results have revealed a very restricted level of EBP implementation among nurses [8][9][10] .…”
Section: Providing a Teaching And Learning Open And Innovative Toolkimentioning
confidence: 99%
“…Evidence-based practice (EBP) is a problem-solving approach to clinical decision-making that integrates the best available scientific evidence with clinical experience and patients' preferences and values 1 . EBP is an instrument of great utility in making clinical decisions in nursing care, helping to reduce healthcare costs 2 and variability in clinical practice, improving the quality of nursing care practice and patients' health outcomes 3 , and increasing job satisfaction of nursing professionals 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Bueno, 1998; Beyea, 2000;Humphris, 1994; Junkin, 2000;Soukoup, 2000;Titler & Mendes, 1999; Youngblut & Brooten, 2000;Hinrichs & Huseboe, 2001; Young, 1999;Charles, 2000;Hunt, 2001; Beel et.al., 1994;Maljanian et. al, 2002;Conn et al; …”
mentioning
confidence: 99%